TEACHING FOREIGN LANGUAGES FOR SPECIFIC PURPOSES: CHALLENGES, PROBLEMS AND SOLUTIONS - Soboļeva, Diāna; Madžule, Inta (Border Security and Management, 2018)
Teaching a foreign language for specific purposes concentrates on the specific needs of the learners, focusing more on language in context and on the course participants` need to acquire a set of professional skills and particular job-related functions. The process of teaching foreign languages in a professional higher education institution is a unique and differs in many aspects, it is directed and addresses immediate and very specific needs, moreover the trend of educational paradigm nowadays is the competency building approach which in turn involves the development of learners` ability to apply existing knowledge and skills in order to solve specific practical work –related problems. The paper is the result of personal professional teaching experience as well as it contains theoretical analysis of teaching foreign language for specific purposes as well as authors reveal the current challenges that teachers encounter in the process of teaching language for specific purposes in the State Border Guard College of the Republic of Latvia.